STRATEGI PEMASARAN GLOBAL DAN RISET PASAR TERHADAP PENJUALAN BATIK DALAM MENGHADAPI PERSAINGAN (Studi Kasus Industri Batik Tulis Giriloyo) - Khotiza Anisa; Wildan Izzaty; Hari Setiawan Saragih; Suhairi Suhairi (Universitas Labuhanbatu, 2022)
Marketing strategy is one way of winning a sustainable competitive advantage whether it is for a company that produces goods or services. The market competition is so much to be a challenge for entrepreneurs.One of the industry producing batik in Indonesia is in Wukirsari Village.The purpose of this study is to analyze the marketing strategy of the global industry is batik Giriloyodalam the face of competition.In this study the author uses the descriptive qualitative method where data collection techniques used is literature study. The results showed that the marketing strategy for the global industry is batik tulis Giriloyo is a strategy of product (product), pricing strategy (price), the strategy of promotion (promotion) and distribution strategy (placement) which commonly called the 4P.